1987
DOI: 10.1111/j.1476-5381.1987.tb08972.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IgE‐dependent histamine release from human dispersed lung mast cells by anti‐allergic drugs and salbutamol

Abstract: The ability of the anti‐allergic drugs, sodium cromoglycate (SCG), lodoxamide, traxanox, RU31156 and the β‐adrenoceptor agonist sulbutamol to inhibit IgE‐dependent histamine and prostaglandin D2 (PGD2) release was assessed using human dispersed lung mast cells. The anti‐allergic drugs were weak inhibitors of histamine release, high concentrations (100–1000 μm) producing < 35% inhibition. Salbutamol produced 39% inhibition at 10 μm. The efficacy of both SCG and salbutamol was inversely related to the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
121
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(132 citation statements)
references
References 38 publications
10
121
0
1
Order By: Relevance
“…In contrast to the results with PDE inhibitors and beclomethasone, salbutamol was effective in suppressing mast cell-derived histamine release. This is consistent with the findings of both Peters et al (1982) and Church & Hiroi (1987) who demonstrated that02 agonists could inhibit histamine release from human dispersed mast cells, an effect mediated by /2 receptors present on mast cells in human lung (Butchers et al, 1980). …”
Section: Discussionsupporting
confidence: 82%
“…In contrast to the results with PDE inhibitors and beclomethasone, salbutamol was effective in suppressing mast cell-derived histamine release. This is consistent with the findings of both Peters et al (1982) and Church & Hiroi (1987) who demonstrated that02 agonists could inhibit histamine release from human dispersed mast cells, an effect mediated by /2 receptors present on mast cells in human lung (Butchers et al, 1980). …”
Section: Discussionsupporting
confidence: 82%
“…In addition, histamine is a transmitter molecule in inflammatory processes and induces burning sensations (63)(64)(65)(66)(67), leading to itching or pain (68,69). Histamine release occurs from vesicles in mast cells or basophils in IgE-mediated allergic reactions (70). This leads to the activation of keratinocytes, which in turn release a transmitter to excite free nerve endings in the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] However, it has become clear that rodent MCs are somewhat different from their human counterparts in terms of their sensitivity to some cytokines and drugs and their receptor expression profiles such as for Fc␥R. 3,[10][11][12][13] It is also observed that the level of IgE-dependent TNF-␣ production by human MCs is quite low compared to that by rodent MCs. 3,4,14 Therefore, it is now necessary to determine if human MCs express TLR4.…”
Section: Introductionmentioning
confidence: 99%